The Domination Complexity and Related Extremal Values of Large 3D Torus. (2nd July 2018) - Shao, Zehui; Xu, Jin; Sheikholeslami, S. M.; Wang, Shaohui
Abstract : Domination is a structural complexity of chemical molecular graphs. A dominating set in a (molecular) graph G = V, E is a subset S ⊆ V such that each vertex in V \ S is adjacent to at least one vertex in S . The domination number γ G of a graph G is the minimum size of a dominating set in G . In this paper, computer-aided approaches for obtaining bounds for domination number on torus graphs are here considered, and many new exact values and bounds are obtained.